2020
DOI: 10.1515/jbcpp-2019-0313
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera seed oil partially abrogates 2,3-dichlorovinyl dimethyl phosphate (Dichlorvos)-induced cardiac injury in rats: evidence for the role of oxidative stress

Abstract: ObjectivesCardiovascular diseases are major causes of non-infectious diseases globally. The use of pesticides has been linked with the high global burden of non-communicable diseases. Despite the indiscriminate exposure to dichlorvos (DDVP) by inhalation, no report exists on its possible cardiotoxic effect. This study investigated the cardiotoxicity of DDVP exposure by inhalation and the possible role of Moringa oleifera seed oil.MethodsTwenty-one male rats were randomly assigned into 3 groups. Group A (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…According to The Fourth Universal Definition of In Myocardial Infarction, the pathological analysis denotes MI as myocardial cell death due to prolonged ischemia ( Thygesen et al, 2018 ). MO increased cardiac antioxidant status, which led to the improvement of MI biomarkers, cardiac contractility, morphology of cardiac muscle, inflammatory cytokines, and apoptotic markers ( Panda et al, 2013 ; Panda, 2015 ; Khalil et al, 2020 ; Saka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to The Fourth Universal Definition of In Myocardial Infarction, the pathological analysis denotes MI as myocardial cell death due to prolonged ischemia ( Thygesen et al, 2018 ). MO increased cardiac antioxidant status, which led to the improvement of MI biomarkers, cardiac contractility, morphology of cardiac muscle, inflammatory cytokines, and apoptotic markers ( Panda et al, 2013 ; Panda, 2015 ; Khalil et al, 2020 ; Saka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to DDVP: Group B and C animals were exposed to 98.54g/m 3 of DDVP via inhalation, as Saka et al (2020) reported. In addition, 1ml of the pesticide was soaked in cotton wool and placed in a desiccator.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…Studies have shown that various parts of the plant (especially the leaves, seeds and roots) have medicinal value. Moringa oleifera has been demonstrated to possess analgesic, antipyretic, anti-diabetic, and hypotensive properties (Saka et al, 2020). It has also been reported to exert antioxidant (Charoensin, 2014;Saka et al, 2020), anti-inflammatory (Cheenpracha et al, 2010), and antimicrobial/antibacterial (Rahman et al, 2009) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera has been demonstrated to possess analgesic, antipyretic, anti-diabetic, and hypotensive properties (Saka et al, 2020). It has also been reported to exert antioxidant (Charoensin, 2014;Saka et al, 2020), anti-inflammatory (Cheenpracha et al, 2010), and antimicrobial/antibacterial (Rahman et al, 2009) activities. Although various parts of the plants exert these activities, the leaves have been reported to be commonly used due to its wide range of beneficial biological activities (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation